Estudio de la Iniciativa de Reporte Global (Gri): Empresa de Transporte de Pasajeros Interconexión Express Sas (2022)
For some years now, strategies have been implemented worldwide to counteract the devastating consequences of environmental damage and, hand in hand with this problem, it is also intended to improve people's quality of life. This is why, currently, the GRI standards represent an essential measure with a high level of organizational transparency regarding environmental, social, and economic impacts, revealing their performance and commitment to the three aspects that comprise these reports. (GRI, s.f.).